Triple elimination screening for pregnancy: study at Dokter Soekardjo Hospital - Desy Aprianti; Susanti Ratunanda (ACTA Medical Health Sciences, 2024)
Triple Elimination is an initiative that supports the eradication of mother-to-child transmission of three infectious diseases: HIV, syphilis, and hepatitis B. Common tests for this initiative include anti-HIV, RPR-TP, and HBsAg rapid screenings. This descriptive study aimed to determine the results of these screenings in pregnant women at Dokter Soekardjo Hospital. We used a total sampling method to include a total of 182 pregnant women who met the inclusion criteria. The findings revealed that the majority of pregnant women were in early adulthood (26-35 years) and late adulthood (36-45 years), each comprising 32.96%. Most subjects were housewives (84.61%) who had a senior high school education (38.46%) , and were examined during their third trimester (58.80%). The RPR-TP rapid screening showed reactive results in 7 women (3.84%). No reactive results were found for Anti-HIV, while one woman (0.54%) tested reactive for HBsAg. The third trimester detected the most reactive results, with 6 women showing reactivity: 5 (4.675%) for RPR-TP and 1 (0.93%) for HBsAg. Despite the absence of reactive Anti-HIV results, precautions against HIV transmission during pregnancy are crucial due to the risk of placental infection or damage. The study's RPR-TP results highlight the importance of addressing reactive cases, given their potential impact. Additionally, performing HBsAg tests remains critical due to the risk of chronic HBV infection in babies. DOI : 10.35990/amhs.v3n1.p1-11 REFERENCES Mardiyanti I, Rahayu EP, Zuwariah N, Winoto PMP, Karmila HN. The effectiveness of triple elimination examination (HIV, syphilis, hepatitis), roll over test (ROT) and mean arterial pressure (MAP) and self-hypnosis on emergency management of high-risk pregnant women during pandemic. Bali Medical Journal. 2023 Aug 1;12(2):1995–1997. Wu S, Wang J, Guo Q, Lan H, Sun Y, Ren M, et al. Prevalence of human immunodeficiency virus, syphilis, and hepatitis B and C virus infections in pregnant women: a systematic review and meta-analysis. Clinical Microbiology and Infection. 2023 Aug;29(8):1000–1007. Cohn J, Owiredu MN, Taylor MM, Easterbrook P, Lesi O, Francoise B, et al. Eliminating mother-to-child transmission of human immunodeficiency virus, syphilis and hepatitis B in sub-Saharan Africa. Bulletin of the World Health Organization. 2021 Apr 1;99(4):287–295. Bell L, van Gemert C, Allard N, Brink A, Chan PL, Cowie B, et al. Progress towards triple elimination of mother-to-child transmission of HIV, hepatitis B and syphilis in Pacific Island Countries and Territories: a systematic review. Lancet Regional Health – Western Pacific. 2023 Jun;35:100740. Pijoan DI, Jambi M, Herlambang H, Kusdiyah E, Syauqy A, Fitri AD, et al. Peningkatan Pengetahuan Tentang Triple Elimination. Peraturan Menteri Kesehatan Republik Indonesia No. 52 Tahun 2017. Justiz Vaillant AA, Gulick PG. HIV Disease Current Practice. In: StatPearls. 2020. World Health Organization. HIV and AIDS [Internet]. 2023 [cited 2023 Nov 9]. Available from: https://www.who.int/news-room/fact-sheets/detail/hiv-aids Peeling RW, Mabey D, Kamb ML, Chen XS, Radolf JD, Benzaken AS. Syphilis. Nature Reviews Disease Primers. 2017 Oct 12;3(1):17073. World Health Organization. Syphilis [Internet]. 2023 [cited 2023 Nov 8]. Available from: https://www.who.int/news-room/fact-sheets/detail/syphilis Tripathi N, Mousa OY. Hepatitis B. In: StatPearls [Internet]. 2023 [cited 2023 Nov 8]. Available from: https://www.ncbi.nlm.nih.gov/books/NBK555945/ World Health Organization. Hepatitis B [Internet]. 2023 [cited 2023 Nov 8]. Available from: https://www.who.int/news-room/fact-sheets/detail/hepatitis-b Pedoman Penilaian Alat Kesehatan dan PKRT. Kementerian Kesehatan Republik Indonesia; 2018. Ratih WU. Strategi Pemeriksaan Laboratorium Anti-HIV. Jurnal Farmasi Sains dan Komunitas. 2012;11(2):98–103. Liazmi MC. Hubungan Antara Orientasi Seksual dan Penggunaan Napza Suntik Dengan Kejadian Sifilis pada Pasien HIV/AIDS di RSUD Dr. H. Abdul Moeloek Lampung Tahun 2017–2019. [Lampung]: Universitas Lampung; 2020. Satyaputra F, Hendry S, Braddick M, Sivabalan P, Norton R. The laboratory diagnosis of syphilis. Journal of Clinical Microbiology. 2021 Sep 20;59(10). Mehta P, Grant LM, Reddivari AKR. Viral Hepatitis. [Updated 2024 Mar 10]. In: StatPearls [Internet]. Treasure Island (FL): StatPearls Publishing; 2024 Jan–. Available from: https://www.ncbi.nlm.nih.gov/books/NBK554549/ Abaalkhail F, Al-Hamoudi W, Khathlan A, Alghamdi S, Alghamdi M, Alqahtani S, et al. SASLT practice guidelines for the management of Hepatitis B virus – An update. Saudi Journal of Gastroenterology. 2021;27(3):115. Al Amin M. Klasifikasi Kelompok Umur Manusia Berdasarkan Analisis Dimensifraktal Box Counting dari Citra Wajah dengan Deteksi Tepi Canny. MATHunesa: Jurnal Ilmiah Matematika. 2017. Yanti NID, Krisnana I, Lestari P. Hubungan Tingkat Pendidikan dengan Kepatuhan Antenatal Care pada Primigravida Riwayat Pernikahan Dini. Indonesian Midwifery and Health Sciences Journal. 2021 Jun 23;3(2):98–106. Primayanti I, Danianto A, Jumsa R, Geriputri NN, Andari MY. Gambaran Epidemiologi Faktor Risiko Preeklamsia pada Ibu Hamil. Jurnal Kedokteran Unram. 2022;1:785–788. Brunner L, Chagnon Krief P, Probst I, Abderhalden-Zellweger A, Renteria SC, Vonlanthen J, et al. A narrative review on factors associated with job interruption during pregnancy. International Journal of Occupational Medicine and Environmental Health. 2023 Sep 7;36(3):303–323. Peraturan Menteri Kesehatan Republik Indonesia No. 52 Tahun 2017. Gonçalves B, Ferreira C, Alves CT, Henriques M, Azeredo J, Silva S. Vulvovaginal candidiasis: Epidemiology, microbiology and risk factors. Critical Reviews in Microbiology. 2016 Nov 21;42(6):905–927. Widhyasih RM, Geni L, Fauziah PN, Amalia V. Gambaran Hasil Pemeriksaan Skrining RPR-TP Rapid, Anti-HIV dan HBsAg Pada Ibu Hamil di Puskesmas Kecamatan Ciracas. Jurnal Ilmiah Analis Kesehatan. 2020;6(1):82–90. Domingues RMSM, Szwarcwald CL, Souza Junior PRB, Leal M do C. Prevalence of syphilis in pregnancy and prenatal syphilis testing in Brazil: Birth in Brazil study. Revista de Saúde Pública. 2014 Oct;48(5):766–774. Kresno SB. Diagnosis dan Prosedur Laboratorium. Fakultas Kedokteran Universitas Indonesia; 2010. Han GR. Management of chronic hepatitis B in pregnancy. World Journal of Gastroenterology. 2012;18(33):4517. Armini LN, Setiawati EP, Arisanti N, Hilmanto D. Evaluation of Process Indicators and Challenges of the Elimination of Mother-to-Child Transmission of HIV, Syphilis, and Hepatitis B in Bali Province, Indonesia (2019–2022): A Mixed Methods Study. Tropical Medicine and Infectious Disease. 2023 Nov 3;8(11):492.